Vaccine Mandates, Private Incentives and the Efficient Use of Coronavirus Vaccines - Michael Stolpe (Wirtschaftsdienst)
Abstract From an economic point of view, vaccine mandates are a negative incentive to get vaccinated. Positive incentives that induce unvaccinated individuals just as effectively — such as government-provided cash incentives — can be more flexible and avoid some of the other disadvantages that come with mandates and possibly achieve higher vaccination rates. Given the size of societal benefits from boosting vaccination rates in the fight against SARS-CoV-2, Germany has substantial unused financial leeway to pay for cash incentives. Prudent combinations of cash incentives and vaccine mandates are also worth considering.